Konsep Syeikh Abdurrauf Singkel tentang Kematian dalam Naskah Lubb al-Kashf wa al-Bayan - Mukarrom, Ahwan (ISLAMICA: Jurnal Studi Keislaman, 2009)
The esoteric nature of Indonesian Islam during the 15th â 17th centuries makes it possible for the debate on eschatological issues including the idea of death to flourish. Abdurrauf Singkel was among the Sufis to have lived in this dynamic century and was engaged in the debate on the issue of death. This paper is aimed at discussing his views about death particularly by referring to his Lubb al-Kashf wa al-Bayan. We discover that Singkelâs treatment of death is related to such concepts of body, soul, salvation and human desire. We also find out that his views found a logical consonance with that of the Javanese manuscript called Serat Wirid idajat Djatinamun. Here human desire and destiny is symbolized in color; red symbolizes humanâs anger, black his evil deeds, yellow his mystical attitude, and white his happiness and inner tranquility. The basic argument of the two books is that control of oneâs desire during his/her lifetime will help determine his/her destiny in life to come.